Literature Study: Complementary Therapy in Overcoming Anemia in Pregnant Women - Ummy Khairussyifa; Khairulisni Saniati; Hearty Efifania Ose Payon; Silvia Finida Hannisa; Tria Anita (Lembaga Pengembangan Kinerja Dosen, 2025)
Approximately 40% of pregnant women worldwide experience anemia. Anemia during pregnancy can cause various serious complications, including premature birth, low birth weight, and even increase the risk of maternal and infant death. Complementary therapy can be an alternative for preventing and treating anemia in pregnant women. This study aims to review research articles related to complementary therapy that can be used to treat anemia in pregnant women. Literature searches through academic databases such as Google Scholar, PubMed and ScienceDirect. Literature selection was carried out based on inclusion criteria (scientific articles in the last 5 years, English/Indonesian, relevant topics) and exclusion (irrelevant articles, no abstract/full-text). Interventions such as acupuncture, yoga, traditional herbs, moringa leaves, spinach and beetroot juice can be safe and natural solutions to increase hemoglobin levels. The selection of the appropriate method can be adjusted according to individual preferences, accessibility, and the level of anemia experienced.